EXPERIMENTAL SUBSTANTIATION OF PREVENTION OF BONE METABOLISM DISORDERS IN THE JAWS OF RATS UNDER EXPERIMENTAL PERIODONTITIS - Sukhomeylo, D.O.; Reyzvikh, O.E.; Shnaider, S.A.; Khrystova, М.Т.; Klenovska, S.V. (World of Medicine and Biology, 2023)
The purpose of this study was to investigate the efficacy of prevention of remodeling disorders in the bone tissue of the alveolar process of the rat jaws with periodontitis against the background of alimentary deficiency of vitamin D. The experimental study was conducted on 36 white Wistar rats of both genders (1 month old, weight 100±5 g), which were divided into 3 groups. The degree of atrophy of the alveolar process was assessed. The activity of elastase, acid phosphatase, alkaline phosphatase, calcium and phosphorus content was determined in the homogenates of jaw bone tissue. The result of the analysis indicates the prevalence of osteoresorption processes over osteosynthesis. The proposed therapeutic and prophylactic complex showed a periodontal protective effect, which was formed due to its properties to increase the activity of alkaline phosphatase, calcium and phosphorus content against the background of a decrease in acid phosphatase and elastase in the bone tissue of the rat alveolar processes modeled with alimentary D-deficient periodontitis.
Keywords: experiment; rats; vitamin D deficiency; periodontitis; biochemical parameters; bone metabolism